Cloning and expression of a C3H-type zinc finger protein gene BoCCCH2 from Brassica oleracea var. italica - JIANG Ming; LIU Qing’e; ZHANG Yanru; ZHU Qi; GONG Xiu; YU Keke; ZHOU Xiuqian (浙江大学学报. 农业与生命科学版)
Brassica oleracea var. italica is an important vegetable crop worldwide, and in China, Taizhou City of Zhejiang Province is one of the major broccoli production areas. Downy mildew and grey mold rot are two common fungal diseases caused by Hyaloperonospora parasitica and Botrytis cinerea, respectively. In recent years, broccoli production in Taizhou was frequently affected by these two fungal diseases, resulting in yield and quality loss. Broccoli germplasm resources resistance to disease is scarce; therefore, molecular breeding is regarded as an effective solution to solve the problem. This is critically important to isolate genes associated with disease resistance, which will act as potential target genes for broccoli breeding.Zinc finger proteins are kinds of important transcription factors in eukaryotic organisms, which involve in various biological activities, such as replication, transcription, translation, repair, metabolism and signaling. According to the number and order of cysteine and histidine residues, zinc finger proteins were classified into several different types, such as C2H2, C2C2, C2C2C2, C2HC and C3H. For example, C3H-type ones contain one to six typical motifs with three cysteine residues and one histidine residue. However, their functions are little known, and no gene has been reported in broccoli.In this study, a C3H-type zinc finger protein gene BoCCCH2 was isolated from broccoli, and later the expression patterns in different organs as well as leaves infected by H. parasitica and B. cinerea were studied.Results indicated that BoCCCH2 contained no intron, and the full length of coding sequence was 1 740 bp encoding 579 amino acids. The deduced protein sequence contained two ANK domains and two CCCH zinc finger structures, respectively, and the CCCH zinc finger types were C—X8—C—X5—C—X3—H and C—X5—C—X4— C—X3—H. Reverse transcription-polymerase chain reaction results showed that the BoCCCH2 was expressed in roots, leaves, stalks, young siliques, flower buds and flowers, with highest level in roots. Expression levels increased when challenged by both H. parasitica and B. cinerea. When infected by H. parasitica, expression levels increased after 24 h, and decreased after 72 h, while infected by B. cinerea, the highest level was detected after 6 h, and slowed down in 12 h. Homologous sequences were downloaded from NCBI (National Center for Biotechnology Information) website, including Citrus sinensis, Gossypium raimondii, Populus trichocarpa, Ricinus communis, Prunus persica, P. mume, Malus domestica, Fragaria vesca, Phaseolus vulgaris, Glycine soja, B. rapa, Camelina sativa, Capsella rubella, Arabidopsis thaliana and Eutrema salsugineum. Phylogenetic analysis results revealed that BoCCCH2 was grouped with homogeneous sequences from other Cruciferae plants with bootstrap confidence of 100%, and sequences from Leguminosae, Euphorbiaceae and Rosaceae were found on different clades.In conclusion, these results indicate that the BoCCCH2 might play an important role in defense responses challenged by either H. parasitica or B. cinerea. Cloning and expression analysis of BoCCCH2 provide evidence for further studies on gene function.